Extent of university-community engagement of Malaysian academics - Md. Yunus, Aida Suraya; Abd Rahim, Asyirah; Shuib, Munir; Masron, Tarmiji; Azman, Norzaini; Abdul Rahman, Shukran (2013)
According to the Australian Universities Community Alliance (AUCEA) (2006), engagement with the community may result in knowledge transfer and exchange, the commercialisation of intellectual property, the establishment of spin-off companies and joint venture activity between universities and community partner. Although the awareness of the importance of university-community engagement has increased, as reflected by the appointment of the Deputy Vice Chancellor to focus on Industry and Community Network and establishment of the University Community Transformation Centres, generally involvement of Malaysian universities in university-community activities is still not encouraging. This study is an attempt to explore the extent of university-community engagement carried out by academics of higher education institutions in Malaysia. This paper discusses part of the findings of a bigger study that explores various interrelated aspects of university community engagement in higher education institutions. It is aimed to deliberate on the extent that universities in Malaysia are conducting local and cross-border university-community engagement and the extent of academics involvement in university-community engagement programmes.